Traditional birth attendants’ knowledge, preventive and management practices for postpartum haemorrhage in Osun State, Southwestern Nigeria - Deborah Tolulope Esan; Olabisi Helen Ayenioye; Paul Oladapo Ajayi; Adewale Allen Sokan-Adeaga (Scientific Reports, 2023)
Abstract Traditional birth attendants (TBAs) have become an integral part of the workforce providing delivery services in Nigeria due to the limited number of skilled birth attendants and cultural preferences. This study assessed the knowledge, management and preventive practices regarding postpartum haemorrhage (PPH) among TBAs in selected communities in Osun State, Southwest Nigeria. The study employed a descriptive cross-sectional study design and recruited 260 TBAs in four communities in Osun State. Data were collected by means of an adapted semi-structured questionnaire. Data were analysed using SPSS version 23 and summarized using descriptive and inferential statistics (chi-square and logistic regression) with the level of significance set at p < 0.05. The findings indicated that most (71.4%) of the TBAs were cleric, while others were herbalist (28.6%). Although the majority (76.4%) of the TBAs had good knowledge of the causes and warning signs of PPH, a high percentage (69.3%) of TBAs had poor management practices, while 114 (64.1%) TBAs had inadequate preventive practices. Notably, almost none of the participants practised active management of the third stage of labour; the majority of TBAs did not administer any uterotonic drugs to the mother, nor did they deliver the placenta by controlled cord traction. Gender (P = 0.029), educational level (P = 0.035) and average number of births per month (P = 0.001) significantly influenced TBAs’ management practices. Similarly, the TBA type (P < 0.001), average number of births per month (P = 0.003) and experience with formal training (P = 0.005) showed significant associations with TBAs’ preventive practices. Furthermore, TBAs’ preventive practices towards PPH were influenced by the TBA type (OR: 4.23; 95% CI 1.64–10.90). TBA management practices were also influenced by the TBA type (OR: 4.42; 95% CI 2.03–9.61). Traditional birth attendants in this study had poor management and poor preventive practices for postpartum haemorrhage.